Brand Crisis and Legitimacy - Lim, WM; Yap, SF; Tan, L; Lim, TWD (Emerald, 2025)
Purpose: This research aims to provide a state-of-the-art overview of brand crisis and legitimacy. Design/methodology/approach: This research conducts a multi-study systematic literature review where brand crisis and legitimacy are reviewed independently and collectively. Findings: This research provides first-hand evidence to show the paucity of the joint investigation of brand crisis and legitimacy despite their established presence in marketing literature. Noteworthily, this research highlights the richness of brand crisis research, albeit the need for greater theoretical grounding and integration in the field, which nevertheless, could be remedied by the strong theoretical foundations available in the body of knowledge on brand legitimacy. Research limitations/implications: This research demonstrates that brand crisis and legitimacy are two important concepts that hold tremendous promise for developing and safeguarding the relationships that brands foster with their stakeholders. Originality/value: This research offers a seminal state-of-the-art overview of brand crisis and legitimacy, along with promising directions for future research to enrich understanding at the point where brand crisis and legitimacy intersect, thereby safeguarding the legitimacy of brands when they experience a crisis in the marketplace.
Keywords: 35 Commerce, Management, Tourism and Services; 1503 Business and Management; 1505 Marketing; 2202 History and Philosophy of Specific Fields; Business & Management; 3505 Human resources and industrial relations; 3506 Marketing; 3507 Strategy, management and organisational behaviour; Brand crisis; Brand legitimacy; Multi-study; Systematic literature review